Thin-wall honeycomb ceramic with thermal shock resistance and mechanical property and preparation method of thin-wall honeycomb ceramic

By adding vanadium pentoxide and neodymium oxide as composite additives to the honeycomb ceramic raw materials, the problem of insufficient mechanical strength and thermal shock resistance of existing honeycomb ceramic materials is solved, and ceramic materials with low expansion coefficient and high compressive strength are achieved.

CN119613095AActive Publication Date: 2025-03-14JIANGXI KEXING SPECIAL CERAMICS CO LTD +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411789636.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

It is difficult for existing honeycomb ceramic materials to generate sufficient holes and ideal pore structures while maintaining mechanical properties, resulting in problems such as low mechanical strength, limited thermal shock resistance or sintering and shrinkage.

Method used

By adding 2 wt% to 4 wt% vanadium pentoxide and 1 wt% to 9 wt% neodymium oxide to the ceramic raw material as composite additives, synergistically, low expansion coefficient and high compressive strength are achieved.

Benefits of technology

The low coefficient of expansion, high density and high compressive strength of ceramic materials are achieved, and both have good thermal shock resistance and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175001310000111
    Figure BDA0005175001310000111
  • Figure BDA0005175001310000121
    Figure BDA0005175001310000121
  • Figure BDA0005175001310000141
    Figure BDA0005175001310000141
Patent Text Reader

Abstract

The invention discloses a thin-wall honeycomb ceramic with thermal shock resistance and mechanical property and a preparation method thereof. The thin-wall honeycomb ceramic comprises basic powder and a composite additive, the composite additive comprises vanadium pentoxide and neodymium oxide, wherein the addition amount of the vanadium pentoxide is 2-4wt% of that of the basic powder, and the addition amount of the neodymium oxide is 1-9wt% of that of the basic powder. The thermal expansion coefficient of the ceramic is reduced by adding vanadium pentoxide, and the sintering compactness of the ceramic is improved by combining neodymium oxide, so that the thin-wall high-strength honeycomb ceramic is obtained. The 2 wt%-4 wt% of vanadium pentoxide and 1 wt%-9 wt% of neodymium oxide interact with each other to achieve synergistic interaction, so that the low expansion coefficient is achieved. And the prepared sample is relatively small in deformation degree and relatively low in thermal expansion coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to honeycomb ceramics, in particular to a thin-wall honeycomb ceramic having both thermal shock resistance and mechanical properties and a preparation method thereof. Background Art

[0002] Honeycomb ceramic materials are widely used in metallurgy, environmental protection, chemical industry, energy and other fields. They can be used as filter materials, thermal insulation materials, chemical fillers and chemical sensors. In practical applications, honeycomb ceramic materials need to generate as many holes and ideal pore structures as possible while maintaining certain mechanical properties to ensure their own sintering density and thermal shock resistance. However, traditional honeycomb ceramics still have problems such as relatively low mechanical strength, limited thermal shock resistance or sintering shrinkage. In order to further optimize the sintering performance, mechanical properties and thermal shock resistance of honeycomb ceramic materials, and improve their processing efficiency and service life, a high-strength, low-expansion thin-walled honeycomb ceramic and its preparation method are urgently needed.

[0003] Chinese invention patent application CN117720334A discloses a high porosity, thin-walled, high-strength honeycomb ceramic and its preparation method and application. In the invention, silicon dioxide is replaced by metal silicon to achieve the purpose of thinning the honeycomb ceramic wall thickness, increasing the porosity and improving the carrier strength. However, it does not pay attention to the thermal shock resistance of the honeycomb ceramic.

[0004] Chinese invention patent application CN108238785A discloses a method for preparing a thin-walled honeycomb ceramic carrier, which improves the fluidity of the mud material by adding bimodal spherical silicon powder, increases the extrusion speed of the mud blank, reduces the thermal expansion coefficient, and has a thermal shock resistance of 800°C without cracking three times. Chinese invention patent application CN118271107A discloses a cordierite honeycomb ceramic and its preparation method and application, which promotes the growth of cordierite crystals in the A-axis direction and reduces the expansion coefficient of cordierite honeycomb ceramics by adding a mineralizer to the raw materials for preparing cordierite honeycomb ceramics. However, none of the above patent applications pays attention to the density and strength of honeycomb ceramic materials.

[0005] Chinese invention patent application CN114849683A discloses a method for preparing low-deformation ultra-thin-wall honeycomb ceramics, which achieves uniform shrinkage and prevents collapse during firing by inspecting and screening raw materials and improving the order of adding materials and the preparation process. It has a very high yield rate and effectively increases the water absorption of the product and reduces the deformation of the product. However, it does not further investigate the mechanical properties of thin-wall honeycomb ceramic materials.

[0006] Chinese invention patent CN213688012U discloses a high-strength honeycomb ceramic heat storage body, which solves the problem that the existing honeycomb ceramic heat storage body is easily bent and damaged by external stress by setting a base, a fixing plate, a cover plate, a knob, a threaded rod, a clamping plate, a base layer, a first reinforcement layer, a second reinforcement layer and an anti-deformation layer. However, it improves the strength of the heat storage body by strengthening external conditions, and does not pay attention to the density and strength of the honeycomb ceramic itself.

[0007] Chinese invention patent CN214293636U discloses a high-strength thin-walled honeycomb ceramic mold. By improving the structural design of the mold, the strength of the mold carrier produced is enhanced, and the survival rate during the production process is also improved. The patent mainly focuses on the strength of the honeycomb ceramic mold rather than the performance of the honeycomb ceramic itself.

[0008] Chinese invention patent application CN114133229A discloses an calcium feldspar micro-nanoporous insulating refractory material and a preparation method thereof, wherein vanadium pentoxide is mainly used as a mineralizer, which can be used to promote the growth and development of beneficial crystals such as calcium feldspar and mullite, reduce the firing temperature, and promote the sintering reaction. However, its use as a mineralizer does not emphasize its own mechanical properties and thermal shock resistance.

[0009] Chinese invention patent application CN107602120A discloses a method for preparing dense rare earth tantalate high temperature ceramics. The rare earth tantalate high temperature ceramics prepared by this method have the characteristics of high process purity, low impurity content, high density and uniform grain size. Similarly, this patent only describes the density and thermal conductivity of the ceramics added with neodymium oxide, and does not emphasize its thermal expansion coefficient and thermal shock resistance as a high temperature resistant material.

[0010] So far, there has been no report on starting from the raw material formula of ceramic materials and using the synergistic enhancement ability of composite additives to simultaneously improve the sintering properties, mechanical properties and thermal shock resistance of ceramic materials, thereby preparing high-strength and low-expansion thin-walled honeycomb ceramics. Summary of the invention

[0011] In view of the deficiencies of the prior art, the object of the present invention is to provide a thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties and a preparation method thereof, so as to achieve a low expansion coefficient.

[0012] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0013] A thin-wall honeycomb ceramic with both thermal shock resistance and mechanical properties comprises a basic powder and a composite additive; the composite additive comprises vanadium pentoxide added in an amount of 2wt%-4wt% of the basic powder and neodymium oxide added in an amount of 1wt%-9wt% of the basic powder.

[0014] The interaction between 2wt%-4wt% of vanadium pentoxide and 1wt%-9wt% of neodymium oxide can synergistically achieve a low thermal expansion coefficient. The sample has a smaller deformation degree and a lower thermal expansion coefficient.

[0015] In a preferred embodiment of the present invention, the composite additive comprises vanadium pentoxide added in an amount of 2wt%-4wt% of the base powder and neodymium oxide added in an amount of 3wt%-9wt% of the base powder.

[0016] The interaction between 2wt%-4wt% of vanadium pentoxide and 3wt%-9wt% of neodymium oxide can not only synergistically reduce the expansion coefficient, but also stabilize the compressive strength of the samples at above 200 MPa.

[0017] Further preferably, the composite additive comprises vanadium pentoxide added in an amount of 2wt%-4wt% of the base powder and neodymium oxide added in an amount of 3wt%-5wt% of the base powder.

[0018] In a preferred embodiment of the present invention, the composite additive comprises vanadium pentoxide added in an amount of 2wt%-3wt% of the base powder and neodymium oxide added in an amount of 3wt%-9wt% of the base powder.

[0019] The interaction between 2wt%-3wt% of vanadium pentoxide and 3wt%-9wt% of neodymium oxide can not only synergistically reduce the expansion coefficient, but also stabilize the compressive strength of the samples at more than 200 MPa. At the same time, the two can synergistically improve the compressive strength.

[0020] Further preferably, the composite additive comprises vanadium pentoxide added in an amount of 2wt%-3wt% of the base powder and neodymium oxide added in an amount of 3wt%-5wt% of the base powder.

[0021] In a preferred embodiment of the present invention, the base powder comprises the following raw materials in parts by weight: 40-60 parts of bauxite powder, 2-6 parts of cordierite powder, 1-4 parts of kaolin, 0.5-1.5 parts of pyroxene powder, 20-35 parts of mullite powder, 2-4 parts of potassium feldspar, 4-9 parts of raw talc, 2-5‰ of the total mass of the powder as a dispersant, and 0.5-2‰ of the total mass of the powder as a grinding aid.

[0022] In a preferred embodiment of the present invention, the aluminum oxide content of the bauxite powder is greater than 80%; and the kaolin powder is Suzhou kaolin.

[0023] The present invention also discloses a thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties. The thermal expansion coefficient of the thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties is (4.33-4.46)×10 -6 / ℃, and the compressive strength is (189-245)MPa; preferably, the thermal expansion coefficient of the thin-walled honeycomb ceramic with both thermal shock resistance and mechanical properties is (4.33-4.37)×10 -6 / ℃, compressive strength is (225-245)MPa.

[0024] The present invention also discloses a method for preparing the thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties, comprising the following steps:

[0025] S1. Weigh each raw material by weight, and grind it into a ball mill to obtain a mixture;

[0026] S2, adding 1-4% of cellulose by weight of the mixture, 1-3% of palm oil by weight of the mixture, 3-10‰ of polyethylene oxide by weight of the mixture, and 10-20% of deionized water by weight of the mixture to the mixture, and kneading to obtain a kneaded mud segment;

[0027] S3, refining the kneaded mud segment to obtain a refined mud segment;

[0028] S4, pressing the refined mud segment into a desired product using a mold to obtain a wet blank;

[0029] S5, drying the wet blank to obtain a dry blank;

[0030] S6, sintering the dry blank to obtain a finished ceramic product.

[0031] In a preferred embodiment of the present invention, the viscosity of the cellulose in S2 is 90,000-110,000, the palm oil is 26-30 degree palm oil, and the molecular weight of the polyethylene oxide is 1-8 million.

[0032] In a preferred embodiment of the present invention, the rotation speed of the ball mill in S1 is 10-40 rpm, and the ball milling time is 6-10 hours;

[0033] The kneading speed in S2 is 20-40 rpm, and the kneading time is 10-30 minutes;

[0034] The vacuum degree of refining in S3 is 0.06-0.09;

[0035] The sintering temperature in S6 is 1150°C-1600°C, and the sintering time is 8-9h.

[0036] In a preferred embodiment of the present invention, in the preparation method, before S6, the step further includes cutting both ends of the dry blank, and the cutting size is 1-1.20 times the length of the finished ceramic product.

[0037] The beneficial effects of the present invention are:

[0038] The present invention provides a thin-walled honeycomb ceramic with both thermal shock resistance and mechanical properties. Vanadium pentoxide and neodymium oxide are added to the ceramic raw materials to improve the thermal shock resistance and sintering density of the ceramic material. The thin-walled honeycomb ceramic product finally obtained has the characteristics of low expansion coefficient, high density and high compressive strength. The raw material composition of the present invention is simple and the production cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of water absorption of ceramics with 2%-10% vanadium pentoxide added as described in the invention content

[0040] Figure 2 Schematic diagram of thermal expansion coefficient of ceramics with 2%-10% vanadium pentoxide added as described in the invention content

[0041] Figure 3 Schematic diagram of linear shrinkage of ceramics with 2%-10% vanadium pentoxide added as described in the invention content

[0042] Figure 4 Schematic diagram of the true density of ceramics with 2%-10% vanadium pentoxide added as described in the invention content

[0043] Figure 5 Schematic diagram of compressive strength of ceramics with 2%-10% vanadium pentoxide added as described in the invention content

[0044] Figure 6 Schematic diagram of water absorption of 1%-9% neodymium oxide ceramics as described in the invention content

[0045] Figure 7 Schematic diagram of thermal expansion coefficient of 1%-9% neodymium oxide ceramics as described in the invention content

[0046] Figure 8 Schematic diagram of linear shrinkage of 1%-9% neodymium oxide ceramics as described in the invention content

[0047] Fig. 9 Schematic diagram of the true density of the ceramic with 1%-9% neodymium oxide added as described in the invention content

[0048] Fig.10 Schematic diagram of compressive strength of ceramics with 1%-9% neodymium oxide added as described in the invention content DETAILED DESCRIPTION

[0049] In order to verify the effect of different formulas of the above composite additives on the performance improvement of thin-walled honeycomb ceramics, a series of experimental studies were carried out, as follows:

[0050] 1. Effect of vanadium pentoxide addition on ceramic properties

[0051] According to the above method, the raw materials are weighed by weight, 2%-10% of vanadium pentoxide is added to the raw materials, and then the raw materials are put into a ball mill, and the ball mill is performed at a speed of 40 revolutions per minute for 10 hours to obtain a mixture; then the mixture is added to a kneading machine, 4% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 5‰ of 1 million to 8 million molecular weight polyethylene oxide, 15% of deionized water are added, the kneading machine speed is set to 30 revolutions per minute, and kneading is performed for 20 minutes to obtain a kneaded mud segment; the kneaded mud segment is put into a vacuum mud kneading machine, and refined at a vacuum degree of 0.09 to obtain a refined mud segment; the refined mud segments are respectively pressed into samples, the samples are dried, and fired at 1600°C for 3 hours to obtain a thin-walled honeycomb ceramic finished product. The water absorption rate, thermal expansion coefficient, linear shrinkage rate, true density and compressive strength of the sample are obtained by the following detection methods.

[0052] (1) Water absorption test: Weigh the sample and place it in ultrapure water for 45 minutes. Then take it out and absorb the surface water with filter paper and weigh it again. The water absorption rate of the sample is calculated by the increase in weight / initial weight.

[0053] (2) Thermal expansion coefficient detection: Use a thermal expansion measuring instrument to measure the thermal expansion coefficients of samples with different additive contents;

[0054] (3) Linear shrinkage rate detection: record the dimensions of the sample before and after sintering, compare the dimensional changes before and after sintering, and calculate the linear shrinkage rate of the ceramic;

[0055] (4) True density detection: Use a true density measuring instrument to measure the true density of samples with different additive contents;

[0056] (5) Compressive strength test: Use a fully automatic press to test the compressive strength of the sample.

[0057] Figure 1 Water absorption rate of ceramics with different vanadium pentoxide addition amounts. Figure 2 is the thermal expansion coefficient of ceramics with different vanadium pentoxide addition amounts. Figure 3 Linear shrinkage of ceramics with different vanadium pentoxide addition amounts. Figure 4 True density of ceramics with different vanadium pentoxide addition amounts. Figure 5 Compressive strength of ceramics with different vanadium pentoxide addition amounts.

[0058] Depend on Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 It can be seen that with the increase of the amount of vanadium pentoxide added, the water absorption rate of the sample gradually increases, indicating that the addition of vanadium pentoxide plays the role of a pore-forming agent, increases the macroscopic porosity of the sample, and reduces the corresponding thermal expansion coefficient, thereby improving the thermal shock resistance of the sample. From the change in linear shrinkage, it can be seen that with the increase in the amount of addition, the sample as a whole shows a trend of changing from inward contraction to outward expansion. When the amount of addition is between 2% and 4%, the degree of deformation of the sample is small, and the corresponding thermal expansion coefficient is also low. With the increase in the amount of addition, the true density of the sample gradually increases, and the compressive strength shows a trend of first increasing and then decreasing. The true density and compressive strength of the sample with added vanadium pentoxide are greater than those of the original sample without addition, which also shows that the sintering density and strength of the sample with added vanadium pentoxide have been improved to a certain extent compared with the original sample.

[0059] 2. Effect of neodymium oxide addition on ceramic properties

[0060] According to the above method, the raw materials are weighed by weight, 1%-9% of neodymium oxide is added to the raw materials, and then the raw materials are put into a ball mill, and the ball mill is performed at a speed of 40 revolutions per minute for 10 hours to obtain a mixture; then the mixture is added to a kneading machine, 4% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 5‰ of 1 million to 8 million molecular weight polyethylene oxide, 15% of deionized water are added, the kneading machine speed is set to 30 revolutions per minute, and kneading is performed for 20 minutes to obtain a kneaded mud segment; the kneaded mud segment is put into a vacuum mud kneading machine, and refined at a vacuum degree of 0.09 to obtain a refined mud segment; the refined mud segments are respectively pressed into samples, the samples are dried, and fired at 1600°C for 3 hours to obtain a thin-walled honeycomb ceramic finished product. The water absorption rate, thermal expansion coefficient, linear shrinkage rate, true density and compressive strength of the sample are obtained by the following detection methods.

[0061] (1) Water absorption test: Weigh the sample and place it in ultrapure water for 45 minutes. Then take it out and absorb the surface water with filter paper and weigh it again. The water absorption rate of the sample is calculated by the increase in weight / initial weight.

[0062] (2) Thermal expansion coefficient detection: Use a thermal expansion measuring instrument to measure the thermal expansion coefficients of samples with different additive contents.

[0063] (3) Linear shrinkage rate detection: record the dimensions of the sample before and after sintering, compare the dimensional changes before and after sintering, and calculate the linear shrinkage rate of the ceramic;

[0064] (4) True density detection: Use a true density measuring instrument to measure the true density of samples with different additive contents;

[0065] (5) Compressive strength test: Use a fully automatic press to test the compressive strength of the sample.

[0066] Figure 6 The water absorption rate of ceramics with different neodymium oxide addition amounts. Figure 7 is the thermal expansion coefficient of ceramics with different neodymium oxide addition amounts. Figure 8 Linear shrinkage of ceramics with different neodymium oxide addition amounts. Fig. 9 is the true density of ceramics with different neodymium oxide addition amounts. Fig.10 The compressive strength of ceramics with different neodymium oxide addition amounts.

[0067] Depend on Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 It can be seen that with the increase of neodymium oxide addition, the water absorption of the sample first increases and then decreases, the thermal expansion coefficient gradually increases, the linear shrinkage rate gradually decreases, the compressive strength first increases and then decreases, and the true density gradually increases. Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 By comparison, the compressive strength of the ceramic samples with added neodymium oxide has been greatly improved compared to the ceramic samples with added vanadium pentoxide, and in the range of 3%-9% addition, the compressive strength of the samples is stable at more than 200MPa. A small amount of neodymium oxide plays a "spot welding" role during high-temperature sintering, improving the mechanical properties without causing a decrease in porosity, thereby obtaining a result with both high porosity and high mechanical strength. However, the thermal expansion coefficient of the sample with added neodymium oxide is significantly increased compared to the original sample without additives and the sample with added vanadium pentoxide, which means that the addition of neodymium oxide will increase the thermal expansion coefficient of the ceramic, thereby affecting its thermal shock resistance.

[0068] Therefore, based on the above comparative experiments, it is considered to add an appropriate amount of neodymium oxide on the basis of adding 2%-4% vanadium pentoxide, so as to obtain a thin-walled honeycomb ceramic with both high strength and low expansion coefficient.

[0069] 3. Effect of adding 2%-4% vanadium pentoxide and 1%-9% neodymium oxide on ceramic properties

[0070] According to the above method, samples were prepared, and the water absorption, thermal expansion coefficient, linear shrinkage, true density and compressive strength of the samples were measured. Table 1 shows the performance parameters of the samples prepared with different addition amounts of vanadium pentoxide and neodymium oxide.

[0071] Table 1 Performance parameters of samples prepared at different addition amounts of vanadium pentoxide and neodymium oxide

[0072]

[0073]

[0074] The increment column in Table 1 calculates the increment of the thermal expansion coefficient of the experimental group and the thermal expansion coefficient of group 0 (blank control group), and the increment of the compressive strength of the experimental group and the compressive strength of group 0 (blank control group).

[0075] It can be seen from Table 1 that when the amount of vanadium pentoxide added is constant, as the amount of neodymium oxide added increases, the water absorption of the sample first increases and then decreases, the thermal expansion coefficient first decreases and then increases, the linear shrinkage first increases and then decreases, the compressive strength first increases and then decreases, and the true density gradually increases. Combined with the experimental results of a single additive, it can be seen that compared with the single addition of 2%-4% vanadium pentoxide or 3%-5% neodymium oxide, the interaction between vanadium pentoxide added in an amount of 2wt%-4wt% of the base powder and neodymium oxide added in an amount of 1wt%-9wt% of the base powder can synergistically enhance the effect of achieving a low expansion coefficient. The sample has a small degree of deformation and a low thermal expansion coefficient. The interaction between vanadium pentoxide added in an amount of 2wt%-4wt% of the base powder and neodymium oxide added in an amount of 3wt%-9wt% of the base powder can not only synergistically reduce the expansion coefficient, but also stabilize the compressive strength of the sample at more than 200MPa. The interaction between vanadium pentoxide added in an amount of 2wt%-3wt% of the base powder and neodymium oxide added in an amount of 3wt%-9wt% of the base powder can not only synergistically reduce the expansion coefficient, but also stabilize the compressive strength of the sample at more than 200MPa, and the two can synergistically improve the compressive strength. When the addition amount of vanadium pentoxide is 2%-4% and the addition amount of neodymium oxide is 3%-5%, the thermal expansion coefficient and compressive strength of the ceramic are within the optimal range.

[0076] Example 1

[0077] A thin-wall honeycomb ceramic with both thermal shock resistance and mechanical properties is made from the following raw materials in parts by weight (kg): 55 parts of bauxite powder with an aluminum oxide content of more than 80%, 3.5 parts of cordierite powder, 3.5 parts of Suzhou kaolin, 1.5 parts of pyrope powder, 35 parts of mullite powder, 2.5 parts of potassium feldspar, 7.5 parts of raw talc, 3‰ of the total weight of the powder as a dispersant, 2‰ of the total weight of the powder as a grinding aid, 3% of the total weight of the powder as vanadium pentoxide and 4% of neodymium oxide.

[0078] A method for preparing a thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties comprises the following steps:

[0079] (1) Weighing each raw material by weight, placing the raw material into a ball mill, and ball milling the raw material at a speed of 20 revolutions per minute for 10 hours to obtain a mixed material;

[0080] (2) adding the mixture to a kneader, adding 2% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 5‰ of 4 million molecular weight polyethylene oxide, and 20% of deionized water, setting the kneader speed to 30 revolutions per minute, and kneading for 20 minutes to obtain a kneaded mud segment;

[0081] (3) putting the kneaded mud segment into a vacuum mud kneading machine and refining it at a vacuum degree of 0.07 to obtain a refined mud segment;

[0082] (4) using a mold to press into a desired product to obtain a wet blank;

[0083] (5) drying the wet blank to obtain a dry blank;

[0084] (6) cutting the two ends of the dry blank, the cutting size is 1-1.20 times the length of the finished product, and obtaining a cut dry blank;

[0085] (7) The cut dry blank is placed in a kiln and fired at 1150°C to obtain a finished product.

[0086] The performance indicators of the finished ceramic products, such as water absorption, thermal expansion coefficient, linear shrinkage, true density and compressive strength, are tested, as shown in Table 2.

[0087] Table 2 Performance of the finished ceramic product obtained in Example 1

[0088]

[0089] Example 2

[0090] A thin-wall honeycomb ceramic with both thermal shock resistance and mechanical properties is made from the following raw materials in parts by weight (kg): 55 parts of bauxite powder with an aluminum oxide content of more than 80%, 3.5 parts of cordierite powder, 3.5 parts of Suzhou kaolin, 1.5 parts of pyrope powder, 35 parts of mullite powder, 2.5 parts of potassium feldspar, 7.5 parts of raw talc, 3‰ of the total weight of the powder as a dispersant, 2‰ of the total weight of the powder as a grinding aid, 3% of the total weight of the powder as vanadium pentoxide and 3% of the total weight of the powder as neodymium oxide.

[0091] A method for preparing a thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties comprises the following steps:

[0092] (1) Weighing each raw material by weight, placing the raw material into a ball mill, and ball milling the raw material at a speed of 20 revolutions per minute for 10 hours to obtain a mixed material;

[0093] (2) adding the mixture to a kneader, adding 2% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 5‰ of 4 million molecular weight polyethylene oxide, and 20% of deionized water, setting the kneader speed to 30 revolutions per minute, and kneading for 20 minutes to obtain a kneaded mud segment;

[0094] (3) putting the kneaded mud segment into a vacuum mud kneading machine and refining it at a vacuum degree of 0.07 to obtain a refined mud segment;

[0095] (4) using a mold to press into a desired product to obtain a wet blank;

[0096] (5) drying the wet blank to obtain a dry blank;

[0097] (6) cutting the two ends of the dry blank, the cutting size is 1-1.20 times the length of the finished product, and obtaining a cut dry blank;

[0098] (7) The cut dry blank is placed in a kiln and fired at 1150°C to obtain a finished product.

[0099] The performance indicators of the finished ceramic products, such as water absorption, thermal expansion coefficient, linear shrinkage, true density and compressive strength, are tested, as shown in Table 3.

[0100] Table 3 Performance of the finished ceramic product obtained in Example 2

[0101]

[0102] Example 3

[0103] A thin-wall honeycomb ceramic with both thermal shock resistance and mechanical properties is made from the following raw materials in parts by weight (kg): 55 parts of bauxite powder with an aluminum oxide content of more than 80%, 3.5 parts of cordierite powder, 3.5 parts of Suzhou kaolin, 1.5 parts of pyrope powder, 35 parts of mullite powder, 2.5 parts of potassium feldspar, 7.5 parts of raw talc, 3‰ of the total weight of the powder as a dispersant, 2‰ of the total weight of the powder as a grinding aid, 3% of the total weight of the powder as vanadium pentoxide and 5% of neodymium oxide.

[0104] A method for preparing a thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties comprises the following steps:

[0105] (1) Weighing each raw material by weight, placing the raw material into a ball mill, and ball milling the raw material at a speed of 20 revolutions per minute for 10 hours to obtain a mixed material;

[0106] (2) adding the mixture to a kneader, adding 2% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 5‰ of 4 million molecular weight polyethylene oxide, and 20% of deionized water, setting the kneader speed to 30 revolutions per minute, and kneading for 20 minutes to obtain a kneaded mud segment;

[0107] (3) putting the kneaded mud segment into a vacuum mud kneading machine and refining it at a vacuum degree of 0.07 to obtain a refined mud segment;

[0108] (4) using a mold to press into a desired product to obtain a wet blank;

[0109] (5) drying the wet blank to obtain a dry blank;

[0110] (6) cutting the two ends of the dry blank, the cutting size is 1-1.20 times the length of the finished product, and obtaining a cut dry blank;

[0111] (7) The cut dry blank is placed in a kiln and fired at 1150°C to obtain a finished product.

[0112] The performance indicators of the finished ceramic products, such as water absorption, thermal expansion coefficient, linear shrinkage, true density and compressive strength, are tested, as shown in Table 4.

[0113] Table 4 Performance of the finished ceramic product obtained in Example 3

[0114]

[0115] The above embodiments are intended to illustrate the present invention, not to limit the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only intended to illustrate the specific working principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall all fall within the scope of the present invention to be protected. The scope of protection of the present invention shall be defined by the attached claims and their equivalents.

Claims

1. A thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties, characterized in that: It comprises a basic powder and a composite additive; the composite additive comprises vanadium pentoxide added in an amount of 2wt%-4wt% of the basic powder and neodymium oxide added in an amount of 1wt%-9wt% of the basic powder.

2. The thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties according to claim 1, characterized in that: The composite additive comprises vanadium pentoxide added in an amount of 2wt%-4wt% of the base powder and neodymium oxide added in an amount of 3wt%-9wt% of the base powder.

3. The thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties according to claim 1, characterized in that: The composite additive comprises vanadium pentoxide added in an amount of 2wt%-3wt% of the base powder and neodymium oxide added in an amount of 3wt%-9wt% of the base powder.

4. The thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties according to claim 1, characterized in that: The base powder comprises the following raw materials in parts by weight: 40-60 parts of bauxite powder, 2-6 parts of cordierite powder, 1-4 parts of kaolin, 0.5-1.5 parts of pyrope powder, 20-35 parts of mullite powder, 2-4 parts of potassium feldspar, 4-9 parts of raw talc, 2-5‰ of the total mass of the powder as a dispersant, and 0.5-2‰ of the total mass of the powder as a grinding aid.

5. The thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties according to claim 4, characterized in that: The aluminum oxide content of the bauxite powder is greater than 80%; the kaolin powder is Suzhou kaolin.

6. A thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties, characterized in that: The thermal expansion coefficient of the thin-walled honeycomb ceramic with both thermal shock resistance and mechanical properties is (4.33-4.46)×10 -6 / ℃, and the compressive strength is (189-245)MPa; preferably, the thermal expansion coefficient of the thin-walled honeycomb ceramic with both thermal shock resistance and mechanical properties is (4.33-4.37)×10 -6 / ℃, compressive strength is (225-245)MPa.

7. A method for preparing a thin-walled honeycomb ceramic having both thermal shock resistance and mechanical properties as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Weigh each raw material by weight, and grind it into a ball mill to obtain a mixture; S2, adding 1-4% of cellulose by weight of the mixture, 1-3% of palm oil by weight of the mixture, 3-10‰ of polyethylene oxide by weight of the mixture, and 10-20% of deionized water by weight of the mixture to the mixture, and kneading to obtain a kneaded mud segment; S3, refining the kneaded mud segment to obtain a refined mud segment; S4, pressing the refined mud segment into a desired product using a mold to obtain a wet blank; S5, drying the wet blank to obtain a dry blank; S6, sintering the dry blank to obtain a finished ceramic product.

8. The preparation method according to claim 7, characterized in that: The viscosity of the cellulose in S2 is 90,000-110,000, the palm oil is 26-30 degree palm oil, and the molecular weight of the polyethylene oxide is 1-8 million.

9. The preparation method according to claim 7, characterized in that: The ball milling speed in S1 is 10-40 rpm, and the ball milling time is 6-10 hours; The kneading speed in S2 is 20-40 rpm, and the kneading time is 10-30 minutes; The vacuum degree of refining in S3 is 0.06-0.09; The sintering temperature in S6 is 1150°C-1600°C, and the sintering time is 8-9h.

10. The preparation method according to claim 7, characterized in that: Before S6, the process also includes cutting two ends of the dry blank, wherein the cutting size is 1-1.20 times the length of the finished ceramic product.

Citation Information

Patent Citations

  • Preparation method of dense rare earth tantalate high temperature ceramic

    CN107602120A

  • Preparation method for thin-walled honeycomb ceramic carrier

    CN108238785A

  • Aorthite micro-nano pore heat insulation refractory material and preparation method thereof

    CN114133229A

  • Preparation method of low-deformation ultrathin-wall honeycomb ceramic carrier

    CN114849683A

  • Honeycomb ceramic with high porosity, thin wall and high strength as well as preparation method and application of honeycomb ceramic

    CN117720334A